Analisis Klinis Sirosis Hati Pada Pemeriksaan Ultrasonografi Abdomen Di Rumah Sakit Dr, H, Marzoeki Mahdi Bogor - Krisna Adriyanto; Wiryanto Wiryanto; Suwendra Iwen; Nursama Heru (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2021)
INTRODUCTION. Cirrhosis is a form of liver damage. Cirrhosis of the liver is the final stage of the process of liver fibrosis, which is the consistent from chronic liver disease that the liver cells lose their function. Cirrhosis is most often caused by alcoholism, hepatitis b, hepatitis c and fatty liver but many other charges (Digestive N, Information D. cirrhosis, 2014). OBJECTIVE. To know the effort to depict the cases of cirrhosis of the liver and its signs precisely and accurately by using ultrasound examination METHOD. This research was conducted by qualitative descriptive method. The population is patients who perform abdominal ultrasound examination in Marzuki Mahdi hospital. The sample used was a patient who examined his liver with a diagnosed liver cirrhosis. The number of samples used is 2 patients. RESULTS. After being analyzed and observed, ultrasonography is an appropriate and accurate examination in describing cases of liver cirrhosis. The use of Doppler or laboratory testing is sometimes needed to further confirm the diagnosis of visible signs. CONCLUSION. Based on this research, it can be expected that ultrasound modalities can be used as the first consideration in enforcing liver cirrhosis cases with accurate, fast, cheap and safe results.